Editorial: Corporeality and Subject - Anna Walczak (Jesuit University Ignatianum in Krakow, 2023)
In the modern humanistic and social discourse the questions concerning body and bod[1]iliness become increasingly more important than the questions about the subject and his identity analysed from the perspective of the existing paradigms. Also, the hitherto utter[1]ances referring to the subject which is embodied are increasingly more often criticised. The modern approach to the body and bodiliness changes the narratives concerning subjectivity, as well as the subject and his identity which, intermediated through the body and bodiliness, is created in the cycles of life and in borderline experiences (crises, trau[1]mas) as a result of which a person may experiences somatic changes.